Tuberculosis in the Head and Neck: Changing Trends and Age‐Related Patterns. (3rd June 2021) - Gehrke, Thomas; Hackenberg, Stephan; Tecle, Nyat; Hagen, Rudolf; Scherzad, Agmal
Abstract : Objective: To evaluate changing trends in patient collectives, age‐related patterns of manifestation, and diagnostic pathways of patients with extrapulmonary head and neck tuberculosis (TB), and to provide strategies to fasten diagnosis in these patients. Study design: Case control study. Methods: A 10‐year retrospective analysis of 35 patients diagnosed with extrapulmonary TB in the head and neck at a tertiary university institution from 2009 to 2019, with special focus on the influence of the patient's age on consideration of TB and clinical patterns. Results: The vast majority of patients younger than 40 years had their origin in countries with high TB burden ( P  = .0003), and TB was considered very early as a differential diagnosis ( P  = .0068), while most patients older than 40 years were domestic citizens initially suspected for a malignancy, who more often had an underlying immunosuppressive condition (0.0472). Most frequent manifestations in both groups were the lymph nodes, larynx, and oropharynx. Surprisingly, no differences in the rates of open TB or history of TB infection in the family anamnesis were found. Conclusion: The two groups of patients found most often are younger patients migrating from regions with high TB burden and elderly domestic patients suffering from immunosuppressive conditions, with the latter often being misdiagnosed as malignancies. TB remains an important but difficult differential diagnosis, due to the initially unspecific symptoms and the great variety in the presentation of manifestations in the head and neck. Level of Evidence: 4 Laryngoscope, 131:2701–2705, 2021